English Catholicism, 1558-1642 - Dures, Alan, author.
1 online resource
Keywords: Newly revised and updated, the second edition of English Catholicism 1558-1642 explores the position of Catholics in early modern English society, their political significance, and the internal politics of the Catholic community. The Elizabethan religious settlement of 1559 ostensibly outlawed Catholicism in England, while subsequent events such as the papal excommunication of Elizabeth I, the Spanish Armada, and the Gunpowder Plot led to draconian penalties and persecution. The problem of Catholicism preoccupied every English government between Elizabeth I and Charles I, even if the numbers of Catholics remained small. Nevertheless, a Catholic community not only survived in early modern England but also exerted a surprising degree of influence. Amid intense persecution, expressions of Catholicism ranged from those who refused outright to attend the parish church (recusants) to church papists' who remained Catholics at heart. English Catholicism 1558-1642 shows that, against all odds, Catholics remained an influential and historically significant minority of religious dissenters in early modern England. Co-authored with Francis Young, this volume has been updated to include recent developments in the historiography of English Catholicism. It is a useful introduction for all undergraduate students interested in the English Reformation and early modern English history.